Air dan Peradaban Manusia pada Zaman Bali Kuno - Srijaya, I Wayan; Dedy Prawirajaya R., Kadek (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 21 No 1 (2021)DO - 10.24843/PJIIB.2021.v21.i01.p10, 2021)
Water is one of the natural elements that is needed by living things. Every living thing, including humans, cannot stay without water. Therefore water is one of the basic human needs besides the need for sanitation and shelter. Water functions as a thirst quencher when humans are thirsty, and functions as fertilizer for plants during the dry season. That is why water is indispensable for maintaining the survival of humans and other creatures. Water is also the starting place for the emergence of a human civilization.